Doctoral Education: Global Perspectives - Rudakov, Victor; Yudkevich, Maria (International Higher Education, 2021)
Doctoral education worldwide is characterized by a trend toward diversity and, at the same time, toward unification. There is no such a thing as a standard doctoral education model. The landscape of doctoral education across the world is quite diverse and there is a considerable rise in its variations and flexibility. However, doctoral education has become a global market with flows of international students, faculty, and graduates who create a demand for unification of standards and benchmarking.